PERAN IBU RUMAH TANGGA UNTUK MENINGKATKAN KESEJAHTERAAN KELUARGA DAN PENYERAPAN TENAGA KERJA HOME INDUSTRY BATIK - Zahroh, Hainunatus; Tarman, Manah; Dawam, Aulia (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This research was taken from the phenomena that exist in the village of Tanjung Bumi, Bangkalan Regency. Where the village of Tanjung Bumi has the largest number of home industries compared to other villages, there are 49 batik home industries in Tanjung Bumi and it also attracts more workers to work in the home industry. The purpose of this study was to determine the role of housewives in improving family welfare and employment in the Batik Home industry. The method used in this research is descriptive method, where this method is an overview in the field regarding the role of housewives to improve family welfare and employment in the Batik Home industry by using in-depth interviews. The data used are primary data and secondary data which the researcher then reveals the content or meaning of the predetermined legal rules. The results of this study indicate that before the existence of the batik home industry, most housewives worked only as housewives and waited for their husbands to come work as fishermen, farmers, casual laborers. With the existence of a batik home industry, housewives can help ease the burden on their husbands and increase their income through the production of batik products